1976
DOI: 10.1172/jci108364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physiologic levels of glucagon and growth hormone on human carbohydrate and lipid metabolism. Studies involving administration of exogenous hormone during suppression of endogenous hormone secretion with somatostatin.

Abstract: A B S T R A C T To study the individual effects of glucagon and growth hormone on human carbohydrate and lipid metabolism, endogenous secretion of both hormones was simultaneously suppressed with somatostatin and physiologic circulating levels of one or the other hormone were reproduced by exogenous infusion. The interaction of these hormones with insulin was evaluated by performing these studies in juvenile-onset, insulin-deficient diabetic subjects both during infusion of insulin and after its withdrawal.Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1
3

Year Published

1977
1977
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(57 citation statements)
references
References 49 publications
6
47
1
3
Order By: Relevance
“…Somatostatin, however, does inhibit the release of a variety of other hormones including growth hormone (8). Although this could have influenced the results of our study, it does not seem likely, because Gerich et al (23) replaced growth hormone during somatostatin administration and noted no effect on the plasma glucose concentration. More definitive evidence emerges from our studies in the dog in which intraportal insulin and glucagon replacement during somatostatin administration results in maintenance of NSGP at basal rates (11).…”
Section: Discussionmentioning
confidence: 53%
“…Somatostatin, however, does inhibit the release of a variety of other hormones including growth hormone (8). Although this could have influenced the results of our study, it does not seem likely, because Gerich et al (23) replaced growth hormone during somatostatin administration and noted no effect on the plasma glucose concentration. More definitive evidence emerges from our studies in the dog in which intraportal insulin and glucagon replacement during somatostatin administration results in maintenance of NSGP at basal rates (11).…”
Section: Discussionmentioning
confidence: 53%
“…The relatively benign metabolic decompensation of patient 2 after 3 d of insulin withdrawal supports the view that this form of diabetes might, in fact, be less prone to ketosis than juvenile onset-type diabetes. Similarly, Barnes et al (39) showed a much slower rise in blood glucose and ketone bodies in pancreatectomized patients after insulin deprivation than in juvenile-type diabetics, which reflects the slowed onset of ketoacidosis in the juvenile-type diabetics of Gerich et al (40) during glucagon suppression by somatostatin. The administration of glucagon accelerated the development of ketoacidosis back to where it was before somatostatin administration (40).…”
Section: Discussionmentioning
confidence: 88%
“…In the liver, FFAs are oxidized to ketone bodies, a process predominantly stimulated by glucagon. Increased concentration of glucagon in DKA reduces the hepatic levels of malonyl-CoA by blocking the conversion of pyruvate to acetyl-CoA through inhibition of acetyl-CoA carboxylase, the first ratelimiting enzyme in de novo fatty acid synthesis (63)(64)(65)(66). Malonyl-CoA inhibits carnitine palmitoyl-transferase (CPT)-I, the rate-limiting enzyme for transesterification of fatty acyl-CoA to fatty acyl-carnitine, allowing oxidation of fatty acids to ketone bodies.…”
Section: Lipid and Ketone Metabolismmentioning
confidence: 99%